A miR-130a-YAP positive feedback loop promotes organ size and tumorigenesis - Shen, Shuying; Guo, Xiaocan; Yan, Huan; Lu, Yi; Ji, Xinyan; Li, Li; Liang, Tingbo; Zhou, Dawang; Feng, Xin-Hua; Zhao, Jonathan C; Yu, Jindan; Gong, Xing-Guo; et al. (Cell research, 2015)
Organ size determination is one of the most intriguing unsolved mysteries in biology. Aberrant activation of the major effector and transcription co-activator YAP in the Hippo pathway causes drastic organ enlargement in development and underlies tumorigenesis in many human cancers. However, how robust YAP activation is achieved during organ size control remains elusive. Here we report that the YAP signaling is sustained through a novel microRNA-dependent positive feedback loop. miR-130a, which is directly induced by YAP, could effectively repress VGLL4, an inhibitor of YAP activity, thereby amplifying the YAP signals. Inhibition of miR-130a reversed liver size enlargement induced by Hippo pathway inactivation and blocked YAP-induced tumorigenesis. Furthermore, the Drosophila Hippo pathway target bantam functionally mimics miR-130a by repressing the VGLL4 homolog SdBP/ Tgi. These findings reveal an evolutionarily conserved positive feedback mechanism underlying robustness of the Hippo pathway in size control and tumorigenesis.